ANALISIS PENGARUH PENGGUNAAN E-WALLET TERHADAP TINGKAT INKLUSI KEUANGAN PADA KALANGAN MAHASISWA DI PURWOKERTO - Edgina Aurellia Prasetyo; Sasha Kamila Shaliha; Alfita Zahwarani; Amandamayakosa Kartawijaya (EBID: Ekonomi Bisnis Digital, 2025)
The shift from traditional financial services has been driven by the rapid development of financial technology (fintech). One prominent innovation is the electronic wallet (e-wallet). University students, as individuals who are closely connected to digital technology, often constitute the majority of e-wallet users. This study aims to analyze the influence of e-wallet usage, perceived security and ease of use, as well as perceived usefulness on financial inclusion among university students in Purwokerto. Primary data were collected through questionnaires distributed to students in the Purwokerto area. The study employed multiple linear regression analysis using EViews 13. The results indicate that perceived security and ease of use, along with perceived usefulness, have a significant positive effect on financial inclusion. However, e-wallet usage itself does not show a significant influence on financial inclusion.